Pandangan Tokoh Agama Jungka Gajah Terhadap Arah Kiblat Bagi Orang Yang Jauh Dari Ka’bah - Cut Nazar Mutia Hanum; Ismail Ismail (Islamic Astronomy Department, Sharia and Law Faculty, 2022)
In the performance of prayer services, a person is required to face towards the Qibla as a valid condition of prayer. The understanding of facing the Qibla must be understood properly and optimally so that efforts to face the Qibla can be done properly and precisely. but for people who are far from Mecca and cannot see the Kaaba directly, the majority of scholars only require facing towards the Kaaba. However, when reviewed, the scholars actually have an agreement that for the person who can see the Kaaba, and the person who cannot see the Kaaba but in fact he can have faith to know the direction to the Kaaba. This research tried to find the opinion of jungka Gajah scholars about the law of observing the qibla for those far from the Kaaba and the limits of tolerance for the direction of qibla for people far from the Kaaba. This research tried to find the opinion of jungka Gajah scholars about the law of observing the qibla for those far from the Kaaba and the limits of tolerance for the direction of qibla for people far from the Kaaba. This research is empirical research using a qualitative approach. With data obtained from interviews with religious leaders Jungka Gajah North Aceh. The data obtained using interview techniques and literature studies, then descriptive analysis with stages of reduction and verification. The results of the research obtained showed: Religious leader Jungka Gajah said that the law confronts the direction of the Qibla when the legal prayer is mandatory, if the person can see the kaaba directly, it is mandatory to face the 'ainul Kaaba when praying. And for the person who cannot see the kaaba then the person must have faith in determining the correct direction of the Qibla. And can make the mosque as a benchmark for the direction of the Qibla, if the mosque has been calculated the direction of the Qibla by people who are experts in the field. The direction of the Qibla that can still be tolerated is that if the shift is below 2 degrees, it can still be forgiven. Because the shift of 2 degrees when people perform prayers cannot be clearly seen with the naked eye the shift in the body of the person who performs the prayer.